Prototype modeling of security system with metal detector - Md. Yusof, Hazlina; Toha, Siti Fauziah; Azlan, N.Z.; Zainuddin, F.; Muhida, Riza; Kazim, M. N. F. M. (2007)
The security system provides the ease to people in order to manage their mall easier and this system is concern on the security of each item. This system will provide not only the items identification but also the anti-theft security. Nowadays, each items produced have a barcode that is printed on its surface as product code. The old system seems not to fully utilize the barcode on each item. This system combines the barcode with electromagnetic security strips in order to reduce the security cost. The barcode strip will be developed in two layers, the barcode and the magnetic strip. The system is working such as the customers self service in the library. The items need to be check at the counter before it been taking out from the store. If the item is not registered then, the alarm will give a warning when it passes through the electromagnetic gate. The LabVIEW program developed by National Instrument is found out to be the best selection as the wave recognition to this system. Identification of patrons and materials by barcode is a reliable technique and gave great service when combined with electro-magnetic security device.